ESKAPEE Pathogen Biofilm Control on Surfaces with Probiotic Lactobacillaceae and Bacillus species - Claudio Neidhöfer; Kamni Rathore; Marijo Parčina; Martin A. Sieber (MDPI AG, 2023)
Combatting the rapidly growing threat of antimicrobial resistance and reducing prevalence and transmission of ESKAPEE pathogens in healthcare settings requires innovative strategies, one of which is displacing these pathogens using beneficial microorganisms. Our review comprehensively examines the evidence of probiotic bacteria displacing ESKAPEE pathogens, with a focus on inanimate surfaces. A systematic search was conducted using the PubMed and Web of Science databases on 21 December 2021, and 143 studies were identified examining the effects of Lactobacillaceae and Bacillus spp. cells and products on the growth, colonization, and survival of ESKAPEE pathogens. While the diversity of study methods limits evidence analysis, results presented by narrative synthesis demonstrate that several species have the potential as cells or their products or supernatants to displace nosocomial infection-causing organisms in a variety of in vitro and in vivo settings. Our review aims to aid the development of new promising approaches to control pathogen biofilms in medical settings by informing researchers and policymakers about the potential of probiotics to combat nosocomial infections. More targeted studies are needed to assess safety and efficacy of different probiotic formulations, followed by large-scale studies to assess utility in infection control and medical practice.